Agrifood trade: Changing challenges, changing perspectives on policy and policy research - Díaz-Bonilla, Eugenio; Gautam, Madhur; Glauber, Joseph W.; Martin, Will; Piñeiro, Valeria; Robinson, Sherman; Traoré, Fousseini; Vos, Rob (International Food Policy Research Institute, 2025)
Agrifood trade plays a key role in ensuring food security, providing smallholders and rural traders with better prices for their products in bigger and higher-value markets, improving efficiency in the production and use of natural resources, and increasing consumer access to safer and more diversified and nutritious foods. This chapter reviews the evolution of trade research, with a focus on the contributions made by IFPRI and others, as well as priorities for future research.